An Evaluation of English Textbook “Prospect 2”: Teachers and Teacher Educators’ Perceptions in the Spotlight - Behrooz Ghoorchaei; Ali Derakhshan; Alemeh Ebrahimi (Journal of Modern Research in English Language Studies)
This study endeavored to evaluate the local English textbook named “Prospect 2” taught in junior high schools in Iran based on a group of Iranian EFL teachers and teacher educators’ perspectives. For this purpose, 10 (6 males and 4 females) teacher educators and 117 (54 males and 63 females) junior high school EFL teachers from Golestan Province, Iran took part in this study. To gather the required data, the modified version of Mukundan’s (2011) questionnaire was utilized as a textbook evaluation checklist to investigate the participants’ perspectives toward suitability, strengths, and shortcomings of the book. The outcomes of this research revealed that the participants of the two groups mainly had positive attitudes toward the book. Further findings of this research did not present any significant difference between teachers and teacher educators’ views toward the book. Finally, some concluding remarks regarding the overall findings of the study were presented. Main implications of the study were that teachers should attempt to incorporate suitable and practical methods for the instruction and promotion of the communicative language teaching approach in the class as an approach on which the book is based and try to cater for the shortcomings of the book through providing supplementary materials and alternative activities for the students.